2021
DOI: 10.1111/1462-2920.15553
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive single‐PCR 16S and 18S rRNA community analysis validated with mock communities, and estimation of sequencing bias against 18S

Abstract: Universal primers for SSU rRNA genes allow profiling of natural communities by simultaneously amplifying templates from Bacteria, Archaea, and Eukaryota in a single PCR reaction. Despite the potential to show relative abundance for all rRNA genes, universal primers are rarely used, due to various concerns including amplicon length variation and its effect on bioinformatic pipelines. We thus developed 16S and 18S rRNA mock communities and a bioinformatic pipeline to validate this approach. Using these mocks, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 42 publications
1
61
0
Order By: Relevance
“…To evaluate the real-world extent of primer biases, we compared PCR primers currently in broad use by the marine microbiology community (Table S2) to SSU rRNA sequences extracted from a geographically diverse set of pelagic ocean metagenomes (Fig 1; Table S1). These analyses were based on the percentage of perfect matches between primers and metagenome sequences as a metric to determine potential PCR performance, since previous studies have shown that even a single mismatch can significantly bias results (3, 13).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To evaluate the real-world extent of primer biases, we compared PCR primers currently in broad use by the marine microbiology community (Table S2) to SSU rRNA sequences extracted from a geographically diverse set of pelagic ocean metagenomes (Fig 1; Table S1). These analyses were based on the percentage of perfect matches between primers and metagenome sequences as a metric to determine potential PCR performance, since previous studies have shown that even a single mismatch can significantly bias results (3, 13).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that PCR amplicon sequencing of mock microbial communities can recover known relative and absolute abundances extremely well, and thus provides accurate quantification of natural gene copy abundances (3, 13, 14). In turn, this accuracy allows amplicon data to serve as a ground-truth for modeling / ecological studies by quantifying community members and their dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations